Effect of colourants on the optical characteristics and structure of Y2O3 stabilised tetragonal zirconia ceramic. (30th March 2021) - Chen, Jianfeng; Wen, Ning; Xue, Chundong; Liu, Zhaocen; Liang, Zhuoran; Wang, Bo; Zhao, Lisheng; Dang, Ruijie; Liao, Ningfang; Dai, Guanghai
Abstract: The present study is to investigate the effect of metal oxides Fe2 O3 and CeO2 on the optical characteristics and structure of Y2 O3 stabilised tetragonal zirconia ceramic (Y‐TZP). It is found that the addition of Fe2 O3 and CeO2 not only changes the colour of Y‐TZP, but also reduces the light transmittance. Meanwhile, the scanning electron microscopy (SEM) characterisation and X‐ray diffraction (XRD) analysis show that the combination of Y‐TZP and the colourant is stable and the structure is uniform. Our findings can improve the understanding of coloration of Y‐TZP by metal oxides, and support a quantitative assessment approach for aesthetic performance of dental restoration material.